The effect of Ocimum basilicum on the prevention of postpartum depression symptoms and sleep quality: A triple-blind randomized controlled clinical trial - Monireh Abdi; Elham Rezaei; Mojgan Mirghafourvand; Fatemeh Ebrahimi; Laleh Payahoo; Alireza Shafiei-Kandjani; Solmaz Ghanbari-Homaie (Heliyon)
Background: Postpartum depression is a multifactorial and complex disorder. Various approaches for preventing and treating this condition have been suggested. Nevertheless, there is no definitive proof confirming their efficacy. This study is designed to assess the effectiveness of basil in preventing postpartum depression (primary outcome) and sleep quality (secondary outcome). Methods: This triple-blind parallel clinical trial (participants, the researcher, and the data analyst were blinded to the assigned interventions) included 78 postpartum women at Taleghani Hospital, Tabriz, Iran, between April 2023 and April 2024. Participants who scored 12 or less on the Edinburgh Postnatal Depression Scale (EPDS) were included in the study. The intervention started within 72 h following birth and continued for eight weeks postpartum. The intervention group received two daily capsules containing dried basil leaf powder, while the control group received 500 mg of starch. The EPDS and postpartum sleep quality scale were completed through structured interviews at eight weeks postpartum. The Mann-Whitney U test was used to compare the mean postpartum depression scores before and after the intervention, and ANCOVA was used to compare the mean postpartum sleep quality scores. Results: The median (25th, 75th percentile) depression score after intervention in the basil and placebo groups was 1.0 (0.0, 2.0) and 1.0 (0.0, 3.0), respectively, with no statistically significant difference between the groups (p = 0.966). The mean (standard deviation) sleep quality score after the intervention in the basil and placebo groups was 17.63 (3.44) and 16.15 (3.20), respectively. There was no statistically significant difference in sleep quality scores between the basil and placebo groups (p = 0.400). Conclusion: The results show that basil does not prevent postpartum depression or improve sleep quality. Future studies should investigate the effects of basil at higher doses and in extract form.